Safety and Efficacy of Chest Physiotherapy in Patients With COVID-19: A Critical Review - Abdullahi, Auwal (Frontiers in Medicine, 2020)
The present global pandemic of COVID-19 has brought the whole world to a standstill, causing morbidity, death and changes in personal roles. The commonest causes morbidity and in these patients deaths include pneumonia and respiratory failure, which make the patients to require artificial ventilation and other techniques that can improve respiratory. One of those techniques is chest physiotherapy; and it has been shown to improve gas exchange, reverse pathological progression and reduce or avoid the need for artificial ventilation when it is provided very early in other respiratory conditions. For patients with Covid-19, there is limited evidence on its effect especially in the acute stage ad in patients in ventilators. In contrast, in patients after discharge, chest physiotherapy in form of respiratory muscles training, cough exercise, diaphragmatic training, stretching exercise and home exercise resulted in improved FEV1 (L), FVC (L), FEV1/FVC%, diffusing lung capacity for carbon monoxide (DLCO%), endurance quality of life and anxiety and depression symptoms. However, there are still controversies on whether chest physiotherapy can disperse aerosols and accelerate the rate of spread of the infection especially since Covid-19 is highly contagious. While some authors believe it is possible; others believe the aerosol generated by chest physiotherapy is not with respirable range. Therefore, measures such as use of surgical masks, tele-rehabilitation and self-management tools can be used to limit cross-infection.